A case study on the environmental management and practices of RSC schools - Cutamora, Melanie G., RSC (Animo Repository, 2015)
The study investigated the Environmental Management and Practices of the schools owned by the Congregation of the Reparatrix Sisters of the Sacred Heart. Employing a qualitative case study approach to research by Yin (2009) in analyzing three case study evidences, three cases were investigated from two different types of schools one is offering Preschool education only while the other two are offering complete Basic Education. The study was conducted during the school year 2012-2013. The participants were 9 administrators, 42 teachers, 40 students, 25 parents, 8 canteen personnel and 19 maintenance personnel. Results of the study show that the dimensions affecting the RSC schools environmental awareness endeavors range from the religious/spiritual sphere to basic, concrete practices. Various challenges emerged in the course of the implementation of the environmentally-responsible practices prompting the school authorities to employ different strategies to address such problems. Some of the solutions done have been helpful in resolving the challenges, and leadership, along with other means, plays a vital role in them. Finally, the study reveals the tangible and intangible benefits and advantages reaped by the individuals and the school community as a whole in their journey towards environmental literacy and responsibility.